Social protection: A tool for crime prevention in Nigeria? Case study of Owerri Municipal Local Government Area, Imo State, Nigeria - Kingsley Noble Osuagwu (Hochschule Bonn-Rhein-Sieg, Fachbereich Sozialpolitik und Soziale Sicherung, 2021)
This study intends to contribute to the discourse on social protection and crime. The study assessed social protection as a tool for crime prevention, with bias to Owerri municipal local government area of Imo state, Nigeria as a case study. The study employed a qualitative approach which allowed the researcher to explore experiences and perspectives of selected participants. Purposive sampling was considered appropriate for the defined population. In-depth interview and focus group discussion (FGD) served as data collection instruments. A review of available literature, reports, newspaper publications, reports, and various internet sources were exhaustively utilised to gather secondary data. The study revealed that social protection possesses the potential to prevent crime. The study informed that certain intervention programmes established by the government helped in decreasing crime incidences in the area under study. In addition, the study revealed that social protection enhances wellbeing, empowers people, promotes better living conditions, imbues a sense of belonging and inclusiveness, promotes social stability and does not lead to dependency. However, the study revealed that social protection alone is incapable of eradicating crime.
urn:nbn:de:hbz:1044-opus-60322
Keywords: 360; Social Protection; Crime; Tool; Potential; Nigeria